Independent Country Programme Evaluation of UNDP Contribution - Kuwait - United Nations Development Programme (United Nations, 2018)
The Independent Evaluation Office (IEO) of the United Nations Development Program (UNDP) conducts country evaluations called “Independent Country Programme Evaluations (ICPEs)” to capture and demonstrate evaluative evidence of UNDP’s contributions to development results at the country level, as well as the effectiveness of UNDP’s strategy in facilitating and leveraging national effort for achieving development results. The ICPE for Kuwait was conducted in 2017 as the UNDP Kuwait country programme ends in 2018. Results are expected to feed into the development of the new country programme.